A program for transplantology and its teaching at the Abuali ibn Sino Tajik State Medical University - S. S. Ismoilov; A. R. Dostiyev; M. K. Gulov; A. Kh. Faizulloyev; O. M. Odinayev; S. F. Gulshanova (Трансплантология (Москва), 2018)
The paper discusses the population’s awareness of transplantation of human organs and tissues. In the authors’ opinion, incorporation of transplantology issues into the training program for students is part of the solution of this problem. It is pointed out that there is a need for postgraduate training in transplantology issues. There are available positive results of the discussion of transplantology problems with the interactive participation of trainees within the framework of a research circles for students. The contribution of organizational measures implemented by the Ministry of Health of the Republic of Tajikistan and under the guidance of the Abuali ibn Sino Tajik State Medical University is indicated.